Cost-effectiveness Analysis of Rituximab Maintenance Treatment in Patients With Follicular Lymphoma who Respond to First Line Induction Therapy in Portugal - Susana Carvalho; Marília Gomes; Herlander Marques; Catarina Pereira; Darío Rubio-Rodríguez; Carlos Rubio-Terrés; Carlos Sottomayor (Formifarma, LDA., 2016)
Introduction: To perform a cost-effectiveness analysis of follicular lymphoma maintenance treatment after first-line induction with rituximab compared to observation in Portugal. Methods: A Markov follicular lymphoma model was developed with four health states: progression free survival on first and second lines, progression and death. The transition probabilities between health states were obtained from the PRIMA and EORTC20981 clinical trials and the health states utilities from the literature. The analysis considered the Portuguese National Health Service perspective and includes only direct costs. Resource consumption was estimated by a Portuguese clinical expert panel. The unit costs (€ in 2014) were estimated using Portuguese official databases. Deterministic and probabilistic analyses were performed. Results: In the base case, for a time horizon of 10 years, the cost per life year gained and per quality-adjusted life-year were € 10,634 and € 10,664, respectively. The sensitivity analyses confirmed the stability of the base case for time horizons of 20 and 30 years, varying between € 7,430 and € 7,155. Maintenance with rituximab is cost-effective for a time horizon of 5.5 years (cost per quality-adjusted life-year gained of € 23,616). Conclusion: According to the present model rituximab maintenance treatment of follicular lymphoma patients that respond to first line induction therapy in comparison with observation is cost-effective in Portugal.